DESTRUKTIVNOE INFLUENCE ENDOGENNYH AND EKZOGENNYH FACTOR ON PROFESSIONAL QUALITY OF THE TEACHER - Nina Iliinichna Medvedeva (Вестник Северо-Кавказского федерального университета, 2022)
The factors open In article and condition destroying influences on professionalism of the teacher of the general school. The Author motivates the psychological accompaniment for conservation of health of the teacher.